‘Pawing’ uncertainty! how dogs attenuate the impact of daily hassles at work on uncertainty - Ana Junça-Silva (BMC Psychology, 2023)
Abstract Purpose This study relied on the integrative model of uncertainty tolerance to delineate an argument proposing that daily hassles trigger uncertainty, and this influences adaptive performance. Furthermore, relying on the “furr-recovery method” –where interactions with dogs allow dog owners to recover from negative situations or job demands - this study tested whether having a dog would moderate the relationship between daily hassles and uncertainty. Methodology To test this proposed model, daily data during ten working days was gathered with a sample of white-collar workers who were teleworking (N = 233 × 10 = 2,330). Findings Multilevel results showed that daily hassles influenced adaptive performance via perceived uncertainty. However, the relationship between daily hassles and uncertainty was conditional on the ownership of a dog, in such a way that the relationship became weaker for those who had dogs. That is, those who did not have dogs had increased levels of uncertainty after daily hassles when compared to those who had dogs. Practical implications Managers may consider the adoption of pet-friendly work practices (for instance, telework – working from home allow employees to work nearby and interact with their dogs during worktime) as dogs appear to have a beneficial effect to help employees effectively cope with daily hassles and reduce their uncertain reactions. Originality This study advances knowledge regarding the pawing-effect (the reduced uncertainty to daily hassles on dog owners) on employees’ uncertainty to daily hassles and opens new venues for research regarding their role in work-related outcomes. Further, future research could examine how human-dog interactions or the quality of their relationship may benefit owners and explore the benefits of bringing dogs to work periodically.